The Determinants Of Preeclampsia In Pregnant Women Of Tarakan - Retnowati, Yuni (International Journal of Science, Technology & Management, 2021)
Preeclampsia is hypertension that can affect all organs, occurs after 20 weeks ofgestation, which begins with endothelial dysfunction and decreased organ perfusionoften characterized by proteinuria. Preeclampsia occurs in 5-7% of all pregnanciesand is the leading cause of maternal death in the developing world. The purpose of thisresearch was to identify risk factors associated with the incidence of preeclampsia inpregnant women at the Public health center Karang Rejo Tarakan in 2021. Thisresearch used a case-control study design. The data used secondary data from mothersmedical record with preeclampsia and without preeclampsia in the period 1 July 2020-30 June 2021. The number of samples was 60 cases and controls. Analysis of dataused univariate, bivariat analysis used chi square test. Results: Bivariat analysisshowed that factors associated with preeclampsia were age> 35 years and a history ofhypertension. Conclusion: The most dominant factor related to the incidence ofpreeclampsia in pregnant women is a history of hypertension